Overlapping generations and environmental control. - Marini, Giancarlo; Scaramozzino, Pasquale (Journal of Environmental Economics & Management, 1995)
A continuous-time overlapping generations model is presented to examine intertemporal trade-offs in the use of environmental resources. It is noted that this theoretical framework is especially pertinent in investigating the externalities that arise from consumer heterogeneity and disconnectedness across generations. The trade-off between capital accumulation and the environment is characterized, and the circumstances for an optimal fiscal policy are obtained. It is concluded that the role of government intervention is twofold: It has to acquire intergenerational equity compatible with a time-consistent social welfare criterion and has to rectify intertemporal market failures that arise from the selfish behavior of each generation.